Growth of preference for solitude in urban and rural Chinese adolescents - Chen, Xi; Sun, Xinxin; Wu, Xuan; Liu, Junsheng; Li, Dan; Chen, Xinyin (Frontiers in Psychiatry, 2023)
This study examined to what extent the developmental trajectory of preference for solitude (PFS) differed between urban and rural Chinese adolescents. Adolescents in urban (n = 326,168 boys, Mage =12.00 years, SD = 0.61) and rural (n = 449, 198 boys, Mage =11.82 years, SD = 0.58) regions in China reported their PFS each year from Grade 6 to Grade 8. Latent growth models revealed that adolescents in both urban and rural regions showed an increasing trajectory of PFS. Although urban and rural adolescents did not differ in the initial level of PFS at Grade 6, urban adolescents’ PFS increased faster than that of the rural adolescents. The urban-rural difference in the slope of PFS remained significant after controlling for the associations between the intercept and the slope of PFS and shyness at each time point. In addition, in the rural region, boys showed a faster increase of PFS than girls, yet gender differences in the initial level of PFS and the developmental trajectory in the urban region were nonsignificant. The results indicate that social-cultural contexts may play an important role in shaping the development of adolescents’ PFS.